2019
DOI: 10.1039/c8ra08516a
|View full text |Cite
|
Sign up to set email alerts
|

Facile solvothermal preparation of Fe3O4–Ag nanocomposite with excellent catalytic performance

Abstract: A new Fe3O4–Ag nanocomposite was preparedviasolvothermal method, demonstrating potential application in catalytic degradation of wastewater treatment and composite materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Sarycheva et al reported the utilization of MXene as a SERS substrate for detecting several common dyes with calculated enhancement factors on the level of 10 6 [33]. Compared to the above works, present prepared composite films via self-assembled LB approach showed good SERS performance with simple and organized process, demonstrating potential applications in SERS detections and composite materials [69,70,71,72,73,74,75,76,77].…”
Section: Resultsmentioning
confidence: 94%
“…Sarycheva et al reported the utilization of MXene as a SERS substrate for detecting several common dyes with calculated enhancement factors on the level of 10 6 [33]. Compared to the above works, present prepared composite films via self-assembled LB approach showed good SERS performance with simple and organized process, demonstrating potential applications in SERS detections and composite materials [69,70,71,72,73,74,75,76,77].…”
Section: Resultsmentioning
confidence: 94%
“…The pseudo-second-order model can be demonstrated by Equation (2) [72]:tqt=1k2qe2+tqe where q e is the adsorption uptake at equilibrium, k 2 is the pseudo-second-model rate constant, and q t is the adsorption uptake at time t .…”
Section: Resultsmentioning
confidence: 99%
“…It could be reasonably speculated that the possible loss of the soluble PEO component in our PCL/PEO@PDA-45 composite adsorbent showed an inconspicuous state during the adsorption measurements. The above cyclic adsorption results indicated that the PCL/PEO@PDA composite showed significant adsorption efficiency, stability, and recyclability [59,60,61,62,63,64,65].…”
Section: Resultsmentioning
confidence: 99%